An Assessment of the Determinants of Environmental Costs of Listed Deposit Money Banks in Nigeria - Lamidi, Wasiu Adebayo; Oluwatuyi, Adesola Olufunmilola; Masunda, Tariro; Olagunju, Adebayo (International Journal of Business and Management Future, 2020)
This paper assesses the determinants of environmental costs of Nigerian banking institutions. Looking at the influence of profitability, company size and leverages on environmental cost such as donation, gift and developments, the population of the study are deposit money banks in Nigeria. Using purposive sampling technique, the study selected all fifteen (15) banks listed on the Nigerian Stock Exchange websites as at June 31, 2019 in which their annual reports are available to be extracted. The study utilized archival data i.e the annual report of listed banks from 2014 – 2017 to extract the needed information. Using STATA 14 software, the study conducts diagnostic tests such as heteroskedasticity, multicollinearity and Pearson correlation for data examination. Hence, multiple regression analysis was conducted to investigate the influence of profitability, company size and leverages on environmental costs. The analysis of the study showed that profitability, company size and leverages have positive and significant association with the environmental cost reported by these banks. Therefore, the study recommended that to adapt to the changing system of doing business, accountants ought to be equipped with skills and knowledge about environmental accounting and reporting, and in order to enhance competitiveness, banks must design and apply environmentally friendly strategies.